MRI and Clinical Risk Indicators for Osteomyelitis. Issue 5 (October 2021) - Massel, Dustin H.; Jenkins, Nathaniel W.; Rush, Augustus J.; Trapana, Justin E.; Foremny, Gregory B.; Donnally, Chester J.; Subhawong, Ty; Aiyer, Amiethab
Introduction. The sensitivity and specificity for magnetic resonance imaging (MRI) diagnosis of osteomyelitis is 90% and 80%, respectively; findings include bone marrow edema, T2-weighted image hyperintensity (HI-T2WI), T1-weighted image confluent signal(CS-T1WI), and cortical erosion (CE). The goal is to determine which risk factors and MRI findings are most predictive of osteomyelitis. Materials and Methods. After institutional review board approval, records of patients who underwent bone biopsy of the foot/ankle between 2015 and 2017 were reviewed. Diagnosis was determined histologically. Blinded MRI review identified indicators of osteomyelitis: HI-T2WI, CS-T1WI, ulcer depth, and CE. Bivariate and multivariate regression determined an association between osteomyelitis and radiographic indicators. Results. Of 59 subjects, 41 (69.5%) and 18 (30.5%) had pathologic evidence of osteomyelitis or were indeterminate. The sensitivity and specificity by radiologist diagnosis was 51.4% and 91.7%, respectively. Diabetes (relative risk [RR]=2.9, 95% CI = 1.0.8-7.77, P = .034), CS-T1WI (RR = 1.6, 95% CI = 1.23-2.20, P < .001), and CE (RR = 1.8, 95% CI = 1.34-2.28, P < .001) were risk factors on bivariate analysis. Ulcer depth demonstrated a trend toward statistical significance. Diabetes (RR = 2.4, 95% CI = 1.00-5.69, P = .049) and CE (RR = 1.7, 95% CI = 1.27-2.37, P < .001) were independent risk factors on multivariate analysis. Discussion. Diabetes and CS-T1WI are independent risk factors for pedal osteomyelitis. Patients with diabetes, CS-T1WI, and CE should be evaluated for osteomyelitis with recommendation for bone biopsy in appropriate clinical settings. Levels of Evidence: Level III Retrospective Comparative Study